PELATIHAN PENYELENGGARAAN JENAZAH DI DESA BOTOLEMPANGAN KEC. SINJAI BARAT KABUPATEN SINJAI - Firman, Tasmia; Musliadi , Musliadi; Alawiyah , Desi; Hawirah , Hawirah; Syam , St.Hajrah; Ismawati, Ismawati (LP2M Universitas Islam Ahmad Dahlan, 2024)
Funeral management training plays an important role in ensuring that the funeral process is carried out with full respect and according to religious procedures. The aim of training on handling corpses is to provide knowledge about the correct procedures for handling corpses, ensure respect for corpses, and respect applicable religious and cultural values, especially to the community in Botolempangan Village, West Sinjai District. This training method includes lectures, practice, and question and answer sessions. The program lasts for one day with maximum preparation. This program was successful in providing understanding to the people of Botolempangan Village about the management of corpses in West Sinjai District, Sinjai Regency. This training provides the basic knowledge, practical skills, and cultural and ethical understanding needed to carry out the task of handling corpses properly. Keywords : Training, Funeral Service